Analisis Perbandingan SAIDI-SAIFI Pada Penyulang 20 Kv Sebelum dan Setelah Pemeliharaan di PT PLN (Persero) ULP Meulaboh Kota - Ramadan Agung; Hermansyah Alam; Amani Darma Tarigan (Jurnal Serambi Engineering, 2024)
The population is growing at a slightly faster rate every year. The significant demand for electricity, supplied by electricity companies such as PT PLN (Persero), is also in line with this population growth. To ensure that the needs of the population are met, the reliability of the electricity distribution system is a priority. Performance indicators such as the System Average Interruption Duration Index (SAIDI) and the System Average Interruption Frequency Index (SAIFI) are available for PT PLN (Persero). The lower the SAIDI, the higher the efficiency and reliability of the distribution system. The comparative study of SAIDI and SAIFI on the 20 kV ULP Meulaboh City feeder is included in this study. According to the SAIDI-SAIFI reliability index of this study, SAIDI = 0.97177 hours/customer/year and SAIFI = 3.01215 outages/customer/year were achieved. Based on the SPLN 59:1985 standard for the 20 kV ULP Meulaboh City feeder in 2023 for January to June, this technology is considered reliable.